1995
DOI: 10.1063/1.359516
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the nonreciprocal magneto-optic effect of TM modes using iron garnet double layers with opposite Faraday rotation

Abstract: Garnet films of composition Lu3−xBixFe5−yGayO12 are grown by liquid-phase epitaxy on [111]-oriented substrates of gadolinium gallium garnet. Faraday rotation and saturation magnetization are measured as a function of substitution levels, which range up to x=1.4 and y=1.8, respectively. Nonreciprocal propagation of the TM0 is studied at a wavelength of 1.3 μm. It is shown that the difference between forward and backward propagation constants can be optimized using double layers with opposite sign of the Faraday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Among these methods, adding a compensation wall ͑CW͒ in the MO materials is an efficient way by the introduction of a large jump of gyrotropy near the CW. [14][15][16][17][18] Recently an alternative method utilizing a nanoscale air gap ͑NAG͒ waveguide with MO layer at the top has been proposed for the efficient enhancement of NPS. 21 Theoretical results showed that the NAG waveguide can enhance the NPS almost eight times than the non-NAG waveguide structures.…”
Section: Enhancement Of Nonreciprocal Phase Shift By Magneto-optical mentioning
confidence: 99%
“…Among these methods, adding a compensation wall ͑CW͒ in the MO materials is an efficient way by the introduction of a large jump of gyrotropy near the CW. [14][15][16][17][18] Recently an alternative method utilizing a nanoscale air gap ͑NAG͒ waveguide with MO layer at the top has been proposed for the efficient enhancement of NPS. 21 Theoretical results showed that the NAG waveguide can enhance the NPS almost eight times than the non-NAG waveguide structures.…”
Section: Enhancement Of Nonreciprocal Phase Shift By Magneto-optical mentioning
confidence: 99%
“…Furthermore, several groups have begun to study size reduction of this device. They have considered the use of double-layered garnets [3], compensation walls [4], or garnets bound to high-index contrast slabs [5]. It has been estimated that the length of the isolators can be reduced to a minimum of several hundred micrometers [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent studies (Jacob et al, 1995;Ling, 1994;Wallenhorst et al 1995) attention was paid to the theoretical and experimental studies of not only the Faraday rotation angle, but also to the studies of a state of light polarization and transmission function of the simple resonance objects such as Fabry-Perot resonators. Based on the obtained results authors have concluded that the application of the Fabry-Perot resonator is an effective method for a measuring of the Faraday rotation, especially in the inefficient media.…”
Section: Wwwintechopencom Infrared Radiation 58mentioning
confidence: 99%